Public Value in Clean Water Management at the Local Water Supply Utility (PDAM) Tirta Kerta Raharja (TKR) - Arsid Arsid; Ida Widianingsih; Heru Nurasa; Entang Adhy Muhtar (Journal of Government and Civil Society, 2019)
As a strategic commodity, Indonesia’s constitution mandates the management of clean water to the local government through the Local Water Supply Utility (PDAM) which is also regulated in PP No. 122/2015 concerning Drinking Water Supply Systems. However, the availability of inadequate clean water as well as the limited ability to manage clean water have caused the minimum service target to be optimal in providing clean water. Using Mark Moore’s public value theory, this study aims to determine how the public value of PDAM TKR (Tirta Kerta Raharja) in Tangerang District. This study uses a qualitative approach. Data collection techniques used were observation, in-depth interviews, and documentation studies. The results of the study show that PDAM TKR’s public value has not been internalized optimally, and it requires adaptation to changes in the organizational environment. In addition, the diverse customer characteristics of PDAM TKR require specific strategies to respond to their needs.